Association of dietary inflammatory index and refractive status in American adolescents: NHANES 1999–2008 - Chen, Xiaodong; Li, Xuewei; Xu, Ningda; Li, Jiarui; Guo, Qianwen; Miao, Heng; Wang, Kai; Huang, Lvzhen (Frontiers in Medicine, 2024)
Background: Many specific nutrients were found to be associated with the prevalence of myopia. Currently, the association of dietary patterns and myopia risk has become a hot topic. We aim to explore the relationship of dietary inflammatory index (DII) and refractive status in adolescents. Methods: This study collected information from 7331 participants from the US National Health and Nutrition Examination Survey (NHANES) 2005-2008. Smooth curve fitting and linear regression analysis were used to explore the nonlinear and linear connection between DII and spherical equivalent refraction (SER). The threshold effect of DII on SER was analyzed using a two-piecewise linear regression model. Results: DII was connected with a lower SER which was a shift towards myopia (β: -0.0586; 95% CI: -0.1109 to -0.0063; P<0.05). Compared to the first quartile, the third quartile (β: -0.2512; 95% CI: -0.4952 to -0.0072; P<0.05) and the fourth quartile (β: -0.2905; 95% CI: -0.5030 to -0.0780; P<0.01) were associated with a lower SER. The smooth curve fitting presented a nonlinear connection between DII and SER (turning point: 0.81). When DII < 0.81, DII was not connected with SER (β: -0.0450; 95% CI: -0.0272 to -0.1173; P>0.05); when DII ≥ 0.81, DII was significantly connected with a lower SER (β: -0.1197; 95% CI: -1.1722 to -0.0672; P<0.01). Conclusion: Our findings indicate that a higher DII (≥0.81) may promote the progression of myopia. This study provides dietary recommendations for myopia prevention. Prospective studies are required to verify these findings.